Fragility analysis and estimation of collapse status for transmission tower subjected to wind and rain loads. (January 2016) - Fu, Xing; Li, Hong-Nan; Li, Gang
Highlights: We propose a simplified method to calculate rain load. A methodology of fragility analysis induced by wind and rain loads is proposed. The concept of critical collapse curve (CCC) is presented. The collapse status for tower subjected to wind and rain loads is estimated. Rain load has great influence on tower collapse. Abstract: In this paper, the fragility analysis and concept of critical collapse curve for transmission tower subjected to wind and rain loads are presented to acquire the collapse equivalent basic wind speed and most unfavorable combinations of wind and rain loads corresponding to collapse status. The calculating method for wind and rain loads is simplified and the error analysis is performed to validate its effectiveness. The concept of equivalent basic wind speed is used to conduct the fragility analysis of transmission tower subjected to wind and rain loads which avoid the complex formula of rain load and the choice of different combinations of basic wind speed and rain intensity, and then the concept of critical collapse curve is proposed to evaluate the collapse status of transmission tower. At last the influence of wind attack angle and wind spectrum on the fragility and critical collapse curves is discussed, and results show that the wind attack angle and wind spectrum have a great influence on fragility and critical collapse curves. In this study, it can be seen that the use of equivalent basic wind speed make it possible to conduct the fragility analysis under wind and rain loads and the proposed concept of critical collapse curve is very convenient to evaluate the collapse status for structures subjected to wind and rain loads. In addition, the rain load has a great contribution to the tower collapse and should be paid more attention during severe gales and thunderstorms.